2016
DOI: 10.1039/c6tb01599a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide nanohybrid that photoreleases nitric oxide

Abstract: Covalent functionalization of graphene oxide with a suitable NO photodonor leads to a nanohybrid material that releases NO under visible light and has potential applications in biomedical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Sortino et al reported a modified graphene oxide (GO) nanoplatform in which GO sheets were covalently functionalized with the NO light-release agent NOP1, and the resulting hybrid nanomedicine (GO-NOP1) released a large amount of NO under visible light. 74 Dr Chen et al constructed a new type of nearinfrared-responsive sandwich nano-drug (GO BNN6). Through π-π stacking, graphene oxide (GO) can absorb NIR light and convert photons into active electrons.…”
Section: No Donor Co-assembly Into Nanomaterialsmentioning
confidence: 99%
“…Sortino et al reported a modified graphene oxide (GO) nanoplatform in which GO sheets were covalently functionalized with the NO light-release agent NOP1, and the resulting hybrid nanomedicine (GO-NOP1) released a large amount of NO under visible light. 74 Dr Chen et al constructed a new type of nearinfrared-responsive sandwich nano-drug (GO BNN6). Through π-π stacking, graphene oxide (GO) can absorb NIR light and convert photons into active electrons.…”
Section: No Donor Co-assembly Into Nanomaterialsmentioning
confidence: 99%
“…However, their use is often limited because of reduced water solubility, photostability, prolonged cutaneous photosensitivity, and low selectivity [ 104 ]. For this region, different approaches have been investigated to combine photosensitizing drugs with other carriers such as liposomes [ 105 ], polymer nanoparticles [ 106 , 107 ], gold nanoparticles [ 108 ], carbon nanotubes [ 109 ], graphene’s [ 110 , 111 ] and carbon nanoparticles [ 112 , 113 ]. Recently, Huang et al [ 114 ] prepared a novel theranostic system based on chlorin e6-conjugated C-dots (C-dots-Ce6).…”
Section: Cds For Cancer Therapymentioning
confidence: 99%
“…[17][18][19][20] Since hyperthermia enhances the anticancer activity of Cur, 21 photothermal nanosystems are interesting Cur delivery systems. 22 Two-component nanohybrid composites that integrate the properties of GO with nanoparticles or organic molecules were widely reported in the literature 23,24 and investigated for different applications including drug delivery, 25 NO photorelease, 26 and antibacterial 27 activity. Differently, very few examples of three-component GO-based nanosystems are present in the literature.…”
Section: Introductionmentioning
confidence: 99%